SEDIMENTOLOGY AND SOURCE ROCK EVALUATION OF THE JURASSIC - CRETACEOUS DEPOSITS IN CENTRAL PAHANG, MALAYSIA - AZMI, AZYAN SYAHIRA (2021)
Central Pahang of Malaysia hosted an extensive distribution of continental sediments of Late Jurassic – Early Cretaceous in age, also known as the Tembeling Group, consisting of four formations.